Transvestism Recognized in Ehlers-Danlos Syndrome: Report of Two Cases - Ishiguro, Hiroki; Honobe, Naomi; Suzuki, Takefumi; Tamai, Mariko; Nakane, Takaya (Case Reports in Psychiatry, 2019)
Ehlers-Danlos syndrome (EDS) comprises a series of rare hereditary connective tissue diseases characterized by musculoskeletal, skin, and cardiovascular involvements. EDS may be associated with physical as well as psychological pain that can lead to psychiatric problems. EDS imposes substantial psychological burden on patients, and recent large-scale studies have suggested that patients with EDS have a higher risk of mood disorders than the general population. To the best of our knowledge, we describe, for the first time, the cases of two Japanese patients with EDS complicated with mood disorders who secondarily developed transvestism that was judged strongly related to early stressful situations through childhood and adolescence. The first case was of a man in his mid-30s and the second of a woman in her late 20s. We report on detailed psychosocial data to further discuss the medical management and genetic counseling of such infrequent but challenging conditions. Physicians are advised to be aware of various potential psychological and psychiatric issues that may accompany EDS.